Método da escavação como recurso de ensino e clínico em terapia ocupacional na perspectiva ergológica - Furtado, Eliana Maria Anjos (Universidade do Vale do Rio dos Sinos, 2010)
This thesis was aimed to write about the field of knowledge of Occupational Therapy, intending to approach this field to the field of ergology. The study is theoretically motivated by the assumptions of education, education and work, ergology, knowledge, experience, phenomenology of perception and phenomenological hermeneutics. The main field of study is occupational therapy. The general aim of this study was to investigate whether the proposal?s method of excavation, as a method of teaching and clinical occupational therapy, may be constituted in a Dynamic dispositive to three-pole of approach ergological from the trial and confrontation, between the knowledge produced in this process and knowledge of training, of students participating in the Study Group on Human Activity. This study used the qualitative research, because this is the more appropriate given the specific nature of this study, since it required a variety of materials originating from different sources. This study is qualitative and exploratory, case study. The research also involved survey, interviews and records of systematic observations of the study group on human activities. The research analysis was performed using the triangulation of sources and dialectical hermeneutics. By analyzing the case study was possible to infer that this process, lived in the experience of the group, there was a confrontation between the knowledge of training, the empiricism of the students and the knowledge learned in the experience of the group and also the intersection of this knowledge, enabling to learners to standardize again of training and reinterpretation of everyday life and work. The proposal?s method of excavation was the device that enabled the circularity of the formal knowledge, the empirical? in the various areas where the training takes place, creating the opportunity for students to reassess their knowledge, to produce a new look at the technologies of occupational therapy and experience a new way to analyze the activities from the self-excavation. The proposal?s method also provided reframe and create a new meaning to work activities of students, as well as professional territory, thus ensuring and reaffirming the power of therapeutic activity while respecting their history, temporality, and social context. The purpose of the excavation process, used as a device for analyzing the experiences and perceptions experienced in the group, formed in a Dynamic Device to Three-Pole of the approach ergological, since students who participated in this group, while examining the activities performed, the technologies of Occupational Therapy, teaching practices and their own work activity, they confronted this knowledge, giving new meaning to them and reframing them.
Keywords: Educação e trabalho; Ergologia; Saberes; Experiência; Terapia ocupacional; Método da escavação; Education and work; Ergology; Ergology; Knowledge; Experience; Occupational therapy; Method of excavation; ACCNPQ::Ciências Humanas::Educação